The Intergenerational Effects of Compulsory Schooling - Oreopoulos, Philip; Page, Marianne E.; Stevens, Ann Huff (Journal of Labor Economics, 2006)
This article attempts to improve our understanding of the causal processes that contribute to intergenerational immobility by exploiting historical changes in compulsory schooling laws that affected the educational attainment of parents without affecting their innate abilities or endowments. We examine the influence of parental compulsory schooling on children’s grade‐for‐age using the 1960, 1970, and 1980 U.S. censuses. Our estimates indicate that a 1‐year increase in the education of either parent reduces the probability that a child repeats a grade by between 2 and 4 percentage points.